KNOWLEDGE REGARDING ORAL HEALTH STATUS AMONG OUTPATIENT DEPARTMENT (OPD) OF PRIVATE DENTAL COLLEGE (Baqai Journal of Health Sciences)
Objective: Study aimed to find out the point of consideration and the practices of oral health status among all the patients seen in the outpatient department of a private dental hospital in Karachi. Method: This is a descriptive cross-sectional questionnaire-based study.  Study participants were engaged through (non-probability) convenience sampling method. The self-structured questionnaires were designed. The survey form was filled out by a trained team of dental surgeons. The questions consisted of two parts, the first part comprised of demographic data and the second part was related to the knowledge about oral hygiene practices among outpatient department of private dental college. Result: A total of 382 subjects visiting to out-patient departments were included. It includes 192 male and 190 female patients (mean of 1.50 and standard deviation of 0.26). The frequency, knowledge and awareness of patient’s knowledge were assessed in this study. In this research study, 48.7% of people uses toothpaste to clean their teeth and 51.3% of people not use uses toothpaste, 17.0% of people uses Miswak, 1.0% of people uses charcoal and 3% of people use dental floss to clean their teeth. Conclusion: This survey reveals that oral health amongst study participants was poor and needs to be better. It also showed that population of low socioeconomic area are deficient in awareness and have lack of positive attitude toward dental treatment.